Utility of chloride and adenosine deaminase measurement in cerebrosphinal fluid for the early presumptive diagnosis of tuberculous meningitis - Swanepoel, Hendré (Division of Chemical Pathology, 2017)
Background: Chloride and adenosine deaminase measurements in cerebrospinal fluid are still sporadically requested as part of tuberculous meningitis work-up. In the literature, evidence is contradictory and opinion is divided on their utility in clinical practice. The accuracy of both for the early presumptive diagnosis of tuberculous meningitis was investigated in patients in a region with high prevalence of tuberculosis and HIV infection in order to inform a decision on whether to continue offering these tests to clinicians. Methods: A retrospective descriptive study of diagnostic accuracy was conducted at the National Health Laboratory Service, Groote Schuur Hospital, Cape Town, South Africa. Data were collected on all cerebrospinal fluid specimens submitted for tuberculosis culture between 1 January 2012 and 31 December 2014. Chloride and adenosine deaminase concentrations were compared with automated liquid culture for Mycobacterium tuberculosis as the reference standard. Findings: There were 2531 cerebrospinal fluid specimens submitted for tuberculosis culture during the study period; exclusion of duplicates yielded 2081 specimens. Chloride was requested on 711 (34·2%) specimens; 44 (6·2%) were tuberculosis culture-positive. Adenosine deaminase was requested on 152 (7·3%) specimens; 20 (13·2%) were culture-positive. Chloride sensitivity (<120 mmol/L) for the detection of tuberculous meningitis was 93·2% (95% confidence interval 81·3-98·6), with specificity 62·4% (58·6-66·1), positive predictive value 14% (10·3-18·6), negative predictive value 99·3% (97·9-99·9), positive likelihood ratio 2·48 (2·18-2·81), and negative likelihood ratio 0·109 (0·037-0·326). Adenosine deaminase sensitivity (>6 U/L) was 70% (45·7-88·1), specificity 89·4% (82·8-94·1), positive predictive value 50% (30·6-69·4), negative predictive value 95·2% (89·8-98·2), positive likelihood ratio 6·6 (3·72-11·7), and negative likelihood ratio 0·336 (0·171-0·657). Interpretation: In this patient population chloride and adenosine deaminase showed at best only modest performance as markers of tuberculous meningitis. However, very good negative predictive values could serve to identify patients highly unlikely to have the disease.